Foreign customer satisfaction level towards KFC Holdings (Malaysia) Berhad / Nor Atikah Kamarun Saman - Kamarun Saman, Nor Atikah (Faculty of Business and Management, 2011)
To be successful, organizations must look into the needs and wants of their customers. That is the reason why many researchers and academicians have continuously emphasized on the importance of customer satisfaction. Customer satisfaction means the intention to make future purchases, it is assumed that high levels of attitudinal loyalty are an outcome of high levels of satisfaction. Satisfaction is defined as an emotional post-consumption response that may occur the result of comparing expected and actual performance or it can be an outcome that occurs without comparing expectations. Satisfaction also leads to attitudinal loyalty. In this research, product, services, price and customer service are the elements that can influence foreign customer satisfaction level towards KFC also to be their chosen fast food restaurant. The survey conducted at the KFC restaurants. The sample size for this study is 50 respondents who are all foreigners. Data obtain using two methods that are primary and secondary data. Respondents are required to answer the questionnaire that includes the statement regarding relationship between elements and the level of foreign customer satisfaction towards KFCH. Once the necessary data has been collected, the data will be analyzed and summarize in are ad able and easily interpret able form. The Statistical Package for the Social Science (SPSS)version 14.0 has been used to summarize the data. The results are in the form of reliability testing, frequency and cross tabulation analysis.